Russian Federation : National and Regional Trends in Regulatory Burden and Corruption - World Bank (Washington, DC, 2014)
Using data from business environment and enterprise performance survey (BEEPS) and other enterprise surveys, studies have shown that firm entry, growth and productivity are impeded by corruption and overly burdensome regulation. Most of these studies have been based on cross-country data (e.g. Barseghyan, 2008), or country-specific studies of firms in China (e.g. Cai et al., 2011; Cull and Xu, 2005), Mexico (Bruhn, 2011) and other nations. Other studies, however, are specific to Russia (e.g. Yakovlev and Zhuravskaya, 2007). Cross-regional variation in corruption and regulatory burden in Russia are potentially important factors in explaining differential performance in private sector development, income levels and growth rates. The intended audiences of this note are policymakers and policy analysts in the non-governmental organization (NGO) and academic communities who are interested in regulatory reform, corruption, and related aspects of the business environment in Russia. A broad range of evidence shows that overly burdensome regulation and corruption are significant impediments to firm entry, productivity and growth. Cross-regional variation in corruption and regulatory burden in Russia is a potentially important factor in explaining differential performance in private sector development, income levels and growth rates. Moreover, further research can investigate the extent to which distortions in various regulatory and administrative areas and transactions may be redundant, in their effects on firm entry and growth. Reforms in a limited number of areas may show disappointing results, if there are remaining distortions sufficient to deter entry or expansion. Rent-seekers may be able to substitute one regulatory barrier for another in blocking competitors.